Non-linear correlation between amylase day 2 to day 1 ratio and incidence of severe acute pancreatitis - Hong, Wandong; Zheng, Luyao; Lu, Yajing; Qiu, Minhao; Yan, Ye; Basharat, Zarrin; Zippi, Maddalena; Zimmer, Vincent; Geng, Wujun (Frontiers in Cellular and Infection Microbiology, 2022)
Background: This study aimed to assess that whether the amylase day 2/ amylase day 1 ratio was associated with severe acute pancreatitis (SAP). Methods: We retrospectively enrolled 464 patients with acute pancreatitis. Serum amylase was measured on admission (day 1) and 24 hrs later (day 2). Univariable logistic regression with restricted cubic spline analysis, multivariable logistic analysis and receiver operating characteristic curve analysis were used to evaluate the relationship between the amylase day 2/ amylase day 1 ratio and SAP. Results: A non-linear association between amylase day 2/ amylase day 1 ratio and SAP was observed. Multivariable logistic analysis confirmed that high amylase day 2/ amylase day 1 ratio (≥0.3) was independently associated with development of SAP (OR: 6.62). The area under the receiver operating characteristic curve (AUC) of amylase day 2/ amylase day 1 ratio, as a predictive factor for SAP, were 0.65. When amylase ratio ≥0.3 was counted as 1 point and added into BISAP score to build a new model named BISAPA (BISAP plus Amylase ratio) score (AUC=0.86), it improved diagnostic power of original BISAP score (AUC=0.83) for SAP. With a cut-off value of 3, BISAPA score achieved a sensitivity of 66.0%, specificity of 86.7% and diagnostic accuracy of 84.48%. Conclusions: There is non-linear correlation between amylase day 2 / amylase day 1 ratio and incidence of SAP. BISAPA score might also be a useful tool for the same purpose.